Readmission trends before and after a national reconfiguration of emergency departments in Denmark. Issue 1 (January 2023) - Bogh, Søren Bie; Fløjstrup, Marianne; Möller, Sören; Bech, Mickael; Lassen, Annmarie T; Brabrand, Mikkel; Mogensen, Christian B
Objective: In order to achieve better and more efficient emergency health care, the Danish public hospital system has been reconfigured, with hospital emergency care being centralised into extensive and specialised emergency departments. This article examines how this reconfiguration has affected patient readmission rates. Methods: We included all unplanned hospital admissions (aged ≥18 years) at public, non-psychiatric hospitals in four geographical regions in Denmark between 1 January 2007 and 24 December 2017. Using an interrupted time-series design, we examined trend changes in the readmission rates. In addition to analysing the overall effect, analyses stratified according to admission time of day and weekdays/weekends were conducted. The analyses were adjusted for patient characteristics and other system changes. Results: The seven-day readmission rate increased from 2.6% in 2007 to 3.8% in 2017, and the 30-day rate increased from 8.1% to 11.5%. However, the rates were less than what they would have been had the reconfiguration not been introduced. The reconfiguration reduced the seven-day readmission rate by 1.4% annually (hazard ratio [CI 95%] 0.986 [0.981–0.991]) and the 30-day rate by 1% annually (hazard ratio [CI 95%] 0.99 [0.987–0.993]). Conclusions: Reconfiguration reduced the rate of increase in readmissions, but nevertheless readmissions still increased across the study period. It seems hospitals and policymakers will need to identify further ways to reduce patient loads.